2017
DOI: 10.1177/1367493517729041
|View full text |Cite
|
Sign up to set email alerts
|

The Faces Emotional Coping Scale as a self-reporting instrument for coping with needle-related procedures: An initial validation study with children treated for type 1 diabetes

Abstract: The aim of this study was to determine the concurrent and content validity, sensitivity and inter-rater reliability of the Faces Emotional Coping Scale (FECS) to evaluate the children's anticipation of the level of emotional coping in conjunction with a venepuncture. A total of 153 children with type 1 diabetes and 86 of their parents participated in the study. The age of the children, 76 of whom were boys, ranged from 7 to 18 years. The child and his or her parent reported the child's coping ability, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Before responding, the children were informed that they would receive a gift certificate for the cinema after completion of the questionnaire. Each child and adolescent, and one of their parents as proxy, estimated pain, affective reaction, and emotional coping on the Coloured Analogue Scale (CAS;McGrath et al, 1996 ), the Facial Affective Scale (FAS;McGrath et al, 1996 ), and Faces Emotional Coping Scale (FECS; Nilsson et al, 2017 ) related to insulin injection, application of a needle for continuous subcutaneous insulin infusion (CSII), blood glucose testing, and venipuncture, respectively. Both the child or adolescent and one of their parents also estimated needle-related fear, using the Diabetes Fear of Injection and Self-Testing Questionnaire (D-FISQ; Mollema et al, 20 0 0 ;Simmons et al, 2007 ) for insulin pen injection and blood glucose testing.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before responding, the children were informed that they would receive a gift certificate for the cinema after completion of the questionnaire. Each child and adolescent, and one of their parents as proxy, estimated pain, affective reaction, and emotional coping on the Coloured Analogue Scale (CAS;McGrath et al, 1996 ), the Facial Affective Scale (FAS;McGrath et al, 1996 ), and Faces Emotional Coping Scale (FECS; Nilsson et al, 2017 ) related to insulin injection, application of a needle for continuous subcutaneous insulin infusion (CSII), blood glucose testing, and venipuncture, respectively. Both the child or adolescent and one of their parents also estimated needle-related fear, using the Diabetes Fear of Injection and Self-Testing Questionnaire (D-FISQ; Mollema et al, 20 0 0 ;Simmons et al, 2007 ) for insulin pen injection and blood glucose testing.…”
Section: Data Collectionmentioning
confidence: 99%
“…The instrument was developed in Sweden and was inspired by the Visual CARE Measure ( Place et al, 2016 ). It has been found to be valid for measuring children's ability to cope with their emotions when undergoing needle-related procedures ( Nilsson et al, 2017 ). A 5-point visual scale was used with face symbols, inspired by smileys (which are common on smartphones), ranging from 0, "not at all," to 4, "excellent."…”
Section: Measurementsmentioning
confidence: 99%
“…Inclusion criteria for the larger project were children aged 7-18 years being treated for T1D and their parents; the exclusion criterion was inability to understand or speak Swedish. Some findings of the larger project have been described previously (Hanberger et al, 2021;Nilsson et al, 2017).…”
Section: Methodsmentioning
confidence: 79%
“…Nurses should use the children's own management strategies as well as guiding them through new strategies (Salmela et al, 2010). Young patients can be asked to assess expected and experienced pain, negative affect, and coping related to needle procedures (Nilsson et al, 2017). Also, communication models such as active listening and mirroring help young persons with T1D to express and cope with difficulties in self‐care (Brorsson et al, 2019).…”
Section: How Might This Information Affect Nursing Practice?mentioning
confidence: 99%
“…The item which involved a faces (smileys) scale was easy to use in the interviews. It has been shown that faces make it easier for children to understand and communicate the meaning of emotions [29].…”
Section: Discussionmentioning
confidence: 99%